2021
DOI: 10.1108/apjml-03-2020-0176
|View full text |Cite
|
Sign up to set email alerts
|

The role of social media elements in driving co-creation and engagement

Abstract: PurposeThe purpose of this paper is to develop and empirically test a research model examining the impact of five social media marketing (SMM) elements–entertainment, customization, interactivity, electronic-word-of-mouth (eWOM) and trendiness–on consumers' intent to participate in value co-creation and on consumer–brand engagement (CBE) and perceived brand value in turn.Design/methodology/approachThe research model is tested for wearable healthcare technology, a smart-technology product. Data were collected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 131 publications
(226 reference statements)
1
57
0
5
Order By: Relevance
“…The results showed that interactivity has a positive effect on brand loyalty, and this was supported by prior research which outlined that interactivity (Sohail et al, 2020) was positively associated with brand loyalty. Cheung et al (2021) stated that using interactive features on a brand's social-media channel provide a motivation for targeted consumers to be engaged in information dissemination, thus resulting in greater degrees of enthusiasm among consumers (Vivek et al, 2012). The finding suggests that fast food brands can increase their emphasis on sharing interactive content with their customers by providing different opportunities for them to participate on their social media pages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that interactivity has a positive effect on brand loyalty, and this was supported by prior research which outlined that interactivity (Sohail et al, 2020) was positively associated with brand loyalty. Cheung et al (2021) stated that using interactive features on a brand's social-media channel provide a motivation for targeted consumers to be engaged in information dissemination, thus resulting in greater degrees of enthusiasm among consumers (Vivek et al, 2012). The finding suggests that fast food brands can increase their emphasis on sharing interactive content with their customers by providing different opportunities for them to participate on their social media pages.…”
Section: Discussionmentioning
confidence: 99%
“…Schulze et al (2015) stated that consumers have a tendency to search for relevant brand information on social media channels. In fact, when firms share customized information to match individuals' preferences, they are likely to obtain better brand evaluation and the consumers feel motivated to share such information with their peers on social networks (Cheung et al, 2021). Furthermore, when consumers have higher involvement with the interactive posts of brands, it is common for them to post their thoughts or feelings on their social media pages, thus leading to the formation of consumergenerated marketing (Cheung et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, this work is one in a series of works that approach co-creation using the qualitative method of netnography (Sindhwani and Ahuja 2014;Sorensen et al 2017;Fujita et al 2019). In a similar manner, several works have also conducted an analysis of brand engagement data using interviews and surveys of customers (Kao et al 2016;Choi et al 2016a, b;Zhang et al 2020;Cheung et al 2021); however, the scalability of these techniques has been highlighted as a limitation (Bharti et al 2014).…”
Section: Background On Co-creationmentioning
confidence: 99%
“…Social media is a powerful medium of communication that can shape changes in the thinking, attitude and behaviour of users who use them (Ping et al, 2019). However, these social media platforms need to be utilized in a positive way to facilitate interaction with others (Cheung et al, 2021). The literature on ethical behaviour emphasized that the users must recognize the unethical conduct and the factors to resist such behaviour were determined by family influences, religious values and personal experiences (Khazanch,1995;Abutaleb et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%